Analysis of the concept of «life and death» in proverbs and sayings of the Korean language - Айгожаева, А. Б. (Journal of Oriental Studies, 2017)
In this article the concept of “Life and Death” in Korean culture in the material of proverbs and sayings was analyzed. As a result, the peculiarities of “Life and Death” perception of Korean people, how they perceive “Life and Death” as well as with what they associate “Life and Death” were shown.